2010
DOI: 10.1111/j.1467-8683.2010.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insider Control and Global Benchmarks on Chinese Executive Compensation

Abstract: Research Question/Issue: We investigate the effect of insider control from the managerial power perspective and the global\ud pay benchmarks from the behavioral approach on Chinese executive compensation.\ud Research Findings: Based on a balanced panel sample of 502 Chinese listed firms between 2001 and 2006, we find that both\ud CEO duality and CEO ownership exert significant influence on Chinese executive compensation contracting and they\ud contribute to the high level of executive compensation. We support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 73 publications
6
79
1
Order By: Relevance
“…Kato and Long (2006a) find that executive cash compensation is positively related to firm performance and the pay-for performance link is weaker in State owned firms. Chen et al (2010) also demonstrate a positive correlation of pay to performance. Kato and Long (2006b) find that sales growth is significantly linked to executive compensation.…”
Section: Compensation Mechanismmentioning
confidence: 82%
“…Kato and Long (2006a) find that executive cash compensation is positively related to firm performance and the pay-for performance link is weaker in State owned firms. Chen et al (2010) also demonstrate a positive correlation of pay to performance. Kato and Long (2006b) find that sales growth is significantly linked to executive compensation.…”
Section: Compensation Mechanismmentioning
confidence: 82%
“…Yet Peng (2004) has shown that appointing outside directors to board positions in Chinese firms often serves a symbolic purpose without actually improving corporate governance. In addition, Chen, Liu, and Li (2010), and Ding, Akhtar, and Ge (2006) showed that when Chinese firms set up CCs they tend to appoint directors who believe that CEO compensation should be based on comparison with global peer companies (that tend to pay their CEOs much more). This suggests that while in theory CCs are expected to improve monitoring and constrain CEO compensation, in practice CC members are selected with the intention of favoring higher CEO compensation.…”
Section: Compensation Committee As a Form Of Symbolic Managementmentioning
confidence: 99%
“…They analysed the statistics for 502 Chinese listed SOEs from 2001 to 2006 and concluded that CEOs use their excessive board power to push executive compensation to a high level, which leads to the loss of state-owned properties. CEO duality is in a dominant position in smoothing business; however, it needs a sound legal system and mature financial markets, which are currently absent in China (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, China has reformed its SOEs and has listed them in domestic and foreign stock exchanges (Chen et al, 2010). This reform is an innovative attempt to diversify SOE ownership and increase SOE independence.…”
Section: Discussionmentioning
confidence: 99%